Position for the sprint: a performance analysis of intermediate sprints in the men`s elite omnium points race - Stanley, R.; Wilson, O.; Wainwright, B. (Journal of Science and Cycling, 2022)
Introduction: In the Omnium Points Race, points are awarded to the first 4 participants (sprint ranks) to cross the finish line at the end of every tenth lap (intermediate sprint), with 5 points given to first place, 3 to second, 2 to third, and 1 awarded to fourth with the winner being the participant with the most points at the end. Therefore, there is an advantage to maximising points scored however, there is no research exploring how this is achieved. This study aimed to identify determinants of performance in intermediate sprints during the Men`s Elite Omnium Points Race.